2005
DOI: 10.1055/s-2005-871906
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations and unanswered questions in the diagnosis and treatment of thyroid nodules

Abstract: Recommendations and unanswered questions in the diagnosis and treatment of thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
13

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
(21 reference statements)
0
10
1
13
Order By: Relevance
“…However, several questionnaire studies with European, North American, and Australian endocrinologists repeatedly revealed large discrepancies in the diagnosis and management of thyroid nodules (23)(24)(25)(26). Among other discrepancies, a less frequent application of the fine needle aspiration biopsy (FNAB), more frequent use of thyroid scintigraphy, thyroid US calcitonin (CT), and thyroid peroxidase (TPO) antibody determination for the diagnosis of thyroid nodules in Europe as compared with North America and different strategies for the treatment of thyroid nodules became apparent.…”
Section: Epidemiology and Risks Of Benign And Malignant Thyroid Diseasesmentioning
confidence: 99%
“…However, several questionnaire studies with European, North American, and Australian endocrinologists repeatedly revealed large discrepancies in the diagnosis and management of thyroid nodules (23)(24)(25)(26). Among other discrepancies, a less frequent application of the fine needle aspiration biopsy (FNAB), more frequent use of thyroid scintigraphy, thyroid US calcitonin (CT), and thyroid peroxidase (TPO) antibody determination for the diagnosis of thyroid nodules in Europe as compared with North America and different strategies for the treatment of thyroid nodules became apparent.…”
Section: Epidemiology and Risks Of Benign And Malignant Thyroid Diseasesmentioning
confidence: 99%
“…Vorliegen einer SD-Autonomie und 2. Vorliegen eines malignen Prozesses [1,3,[5][6][7][8]. Des Weiteren kann eine mechanische Beeinträchtigung (Trachea-und/oder Ösophaguskompression), insbesondere bei Vorliegen multinodöser Strumen, von klinischer Bedeutung sein [6,9].…”
Section: Dignität Und Aktivität -Zwei Entscheidende Fragenunclassified
“…Nach älteren internationalen Erhebungen liegt die Karzinomprävalenz in SD-Knoten bei etwa 3-5% [10,11]. Die Daten deutscher Krebsregister zeigen hingegen eine wesentlich niedrigere Karzinomprävalenz von etwa 0,1% [1]. 4.…”
Section: Dignität Und Aktivität -Zwei Entscheidende Fragenunclassified
See 2 more Smart Citations